A preliminary DNA barcode selection for the genus Russula (Russulales, Basidiomycota) - Guo-Jie Li; Rui-Lin Zhao; Chu-Long Zhang; Fu-cheng Lin (Mycology, 2019)
Russula is a worldwid genus which has a high species diversity . Aiming accurate and rapid species identification, candidate genes nLSU (28S), ITS, tef-1α, mtSSU, rpb1, and rpb2, were analysed as potential DNA barcodes. This analysis included 433 sequences from 38 well-circumscribed Russula species of eight subgenera. Two vital standards were analysed for success species identification using DNA barcodes, specifically inter- and intra-specific variations together with the success rates of PCR amplification and sequencing. Although the gap between inter- and intra-specific variations was narrow, ITS met the qualification standards for a target DNA barcode. Overlapping inter- and intra-specific pairwise distances were observed in nLSU, tef-1α, mtSSU, and rpb2. The success rates of PCR amplification and sequencing in mtSSU and rpb1 were lower than those of others. Gene combinations were also investigated for resolution of species recognition. ITS-rpb2 was suggested as the likely target DNA barcode for Russula, owing to the two viatal standards above. Since nLSU has the lowest minimum of inter-specific variation, and tef-1α has the highest overlap between intra- and inter-species variations among the candidate genes, they are disqualified from the selection for DNA barcode of Russula.